STORIES IN THE QUR’AN BETWEEN REALITY AND METAPHOR: A COMPARATIVE STUDY OF MUHAMMAD KHALAFULLAH AND SAYYID QUTB - Walidah, Nurul (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2025)
This study explores the contrasting approaches of Muhammad Ahmad Khalafullah and Sayyid Quthb in interpreting Qur'anic narratives. Khalafullah views these stories as literary-symbolic constructs that do not necessarily reflect historical facts but are intended to evoke moral and spiritual consciousness through aesthetic language. He classifies Qur'anic narratives into three categories: literary-historical, parabolic, and mythological stories. In contrast, Sayyid Quthb asserts that Qur'anic stories possess ontological truth, even though their presentation is thematic, non-chronological, and rhetorically rich. This research employs a qualitative methodology with a library research approach and hermeneutic analysis of the main works of both scholars: al-Fann al-Qashasi fi al-Qur’an al-Karim and at-Tashwir al-Fanni fi al-Qur’an. The findings reveal that their main divergence lies in epistemological orientation: Khalafullah grounds his interpretation in literary symbolism and rational humanism, while Quthb emphasizes divine revelation and da‘wah function. The study concludes that both perspectives significantly contribute to the development of contemporary narrative exegesis and offer a potential foundation for an integrative and contextual approach to understanding Qur'anic stories more comprehensively